Tìm X: X - 636 = 5618
Tìm x
x – 636 = 5618
Tìm x
x – 636 = 5618
Tìm x:
a, x + 1536 = 6924
b, x × 2 = 2826
c, x – 636 = 5618
d, x∶ 3 = 1628
a, x+1536= 6924
b, x-636=5618
c, x:3=1628
giúp mình nhé . Cảm ơn
a, x+1536= 6924
x = 6924 - 1536
x = 5388
b, x-636=5618
x = 5618 + 636
x = 6254
c, x:3=1628
x = 1628 x 3
x = 4884
a x + 1536 = 6924
x = 6924 - 1536
x = 5388
B, x - 636 = 5618
x = 5618 + 636
x = 6254
C, x : 3= 1628
x= 1628 x 3
x=4884
Tìm x
a, x + 1536 = 6924
b, x × 2 = 1284
c, x – 636 = 7892
d, x∶ 7 = 5684
Tìm x ∈ ℤ ,biết:
a ) 3 8 + − 11 8 < x < 22 9 + 5 18 ; b ) − 7 8 + 5 6 < x 24 < 2 3 + − 5 8 ; c ) 1 3 + 1 4 + 1 12 ≤ x ≤ 7 10 + 27 6 ; d ) − 31 14 + 115 161 + 111 74 < x ≤ 6 36 + 9 27 + 48 96
a) – 1 < x < 49 18 => x ∈ {0;1;2}
b) − 1 24 < x 24 < 1 14 => x = 0
c) 2 3 ≤ x ≤ 26 5 => x ∈ {1;2;3;4;5}
d) 0 < x ≤ 1 => x = 1
A) 194 X x = 94090
B) x : 83 = 636 (dư 28)
636-36*x=450
636 - 36 * x = 450
36 * x = 636 - 450
36*x = 186
x =186 : 36
x = \(\frac{32}{6}\approx5,1666666667\)
636 - 36*x = 450
=> 36*x = 636 - 450 = 186
=> x = 186 : 36
=> x = 31/6
x + 1536 = 6924
x * 9 = 2763
x - 636 = 5616
x / 3 = 1628
x+1526=6924
x=6924-1526
x=5398
x*9=2763
x=2763/9
x=307
x-636=5616
x=5616+636
x=6252
x/3=1628
x=1628*3
x=4884
đúng thì tick cho mình nhé